Latitudinal Asymmetry in the Dayside Atmosphere of WASP-43b - Challener, RC; Rustamkulov, Z; Lee, EKH; Lewis, N; Sing, DK; Birkmann, SM; Crouzet, N; Espinoza, N; Manjavacas, E; Oliveros-Gomez, N; Valenti, JA; Yang, J (American Astronomical Society, 2024)
We present two-dimensional near-infrared temperature maps of the canonical hot Jupiter WASP-43b using a phase-curve observation with JWST NIRSpec/G395H. From the white-light planetary transit, we improve constraints on the planet’s orbital parameters and measure a planet-to-star radius ratio of 0.15883−0.00053+0.00056 . Using the white-light phase curve, we measure a longitude of maximum brightness of 6.9−0.°5+0.°5 east of the substellar point and a phase-curve offset of 10.0−0.°8+0.°8 . We also find a ≈4σ detection of a latitudinal hotspot offset of −13.4−1.°7+3.°2 , the first significant detection of a nonequatorial hotspot in an exoplanet atmosphere. We show that this detection is robust to variations within planetary parameter uncertainties, but only if the transit is used to improve constraints, showing the importance of transit observations to eclipse mapping. Maps retrieved from the NRS1 and NRS2 detectors are similar, with hotspot locations consistent between the two detectors at the 1σ level. Our JWST data show brighter (hotter) nightsides and a dimmer (colder) dayside at the shorter wavelengths relative to fits to Spitzer 3.6 and 4.5 μm phase curves. Through comparison between our phase curves and a set of general circulation models, we find evidence for clouds on the nightside and atmospheric drag or high metallicity reducing the eastward hotspot offset.